2005
DOI: 10.1007/s11148-005-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of composite materials in the Si3N4 - BN system

Abstract: The results of a study of the thermophysical properties (thermal diffusivity, heat capacity, heat conductivity, and coefficient of linear thermal expansion) of Si 3 N 4 -BN hot-pressed composite (with BN concentration varying from 10 to 60 wt.%) in the temperature range of 20 -900°C are reported.Ceramic materials intended for service under heavy-duty conditions -high temperatures (up to 1300 -1500°C) and high mechanical loads -must necessarily be tested for thermophysical properties. Knowledge of heat conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, the addition of h-BN content might have negative effects on the bending strength and fracture toughness due to uneven pores distribution in the composites [4,5]. The appropriate adding of sintering additives such as Y 2 O 3 [6], Al 2 O 3 [7] and some other rare-earth oxides [8] could accelerate the sintering process of BN/Si 3 N 4 composites. For example, Li Yongfeng et al [9] studied the effects of the Yb 2 O 3 content from 2wt.% to 15wt.% on the mechanical properties of Si 3 N 4 /BN composites and found that 4wt.% Yb 2 O 3 addition was most beneficial to the flexural strength which reached the value of 264.3 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of h-BN content might have negative effects on the bending strength and fracture toughness due to uneven pores distribution in the composites [4,5]. The appropriate adding of sintering additives such as Y 2 O 3 [6], Al 2 O 3 [7] and some other rare-earth oxides [8] could accelerate the sintering process of BN/Si 3 N 4 composites. For example, Li Yongfeng et al [9] studied the effects of the Yb 2 O 3 content from 2wt.% to 15wt.% on the mechanical properties of Si 3 N 4 /BN composites and found that 4wt.% Yb 2 O 3 addition was most beneficial to the flexural strength which reached the value of 264.3 MPa.…”
Section: Introductionmentioning
confidence: 99%